A comparative assessment of the Integrated Social Forestry Program (ISFP) in two project sites in San Joaquin, Iloilo - Laguda, Alexander Ladrillo (1998.)
This study is an assessment of the Integrated Social Forestry Program (ISFP) implementation in two selected project sites of the Municipality of San Joaquin, Province of Iloilo.
Sotech-Special Problem - (Cert. in Environmental Resource Management) - U. P. in the Visayas
Keywords: Integrated Social Forestry Program -- San Joaquin, Iloilo